"Enjoy your experience": Symbolic violence and becoming a tasteful state cannabis consumer in Canada. (August 2022) - Cormack, Patricia; Cosgrave, James
This article explores the legalization and marketing of recreational cannabis in Canada, specifically the province of Nova Scotia, that has extended state monopoly over sales. Beginning with Howard Becker's classic analysis of "becoming a marijuana user, " this ethnographic investigation of the first day of state cannabis sales utilizes and extends Bourdieusian analyses, particularly by showing how "symbolic violence" and "taste distinctions" work beyond overt class reproduction to establish state classifications and rituals. The practices we observe show state formation in action at the point of sale, including education, warning, prohibition, and promotion. As we demonstrate, the state marketing of cannabis works to invite emotional identification toward becoming the state consumer as an embodied habitus. The citizen is not just redeemed morally by the legal recategorization of cannabis but brought into a new subject position as good consumer citizen at the moment of ritual consumption, that is, brought into a "tasteful state."